2011
DOI: 10.1123/tsp.25.2.233
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Change in Athletes’ Careers: A Scheme of Change for Sport Psychology Practice

Abstract: Throughout their careers, athletes may encounter various changes that interfere with their existing “athletic status quo.” During these transitional periods, change can occur in diverse levels of the athletic experience. In this paper we introduce a “scheme of change for sport psychology practice” (SCSPP) to describe typical characteristics of athletes’ change-events and processes. The SCSPP focuses on: (a) the stages that unfold as athletes encounter and address changes in their careers, and (b) the psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 28 publications
2
64
0
Order By: Relevance
“…Nearly seventy eight per cent of transitions were normative in nature (e.g., scores, selections, entry in a training centre, success in academic examination) and is comparable to other studies (e.g., Samuel & Tenenbaum, 2011). A majority (85%) of these normative transitions was perceived as positive transitions as they were negotiated effectively without any particular assistance (Sinclair & Orlick, 1993).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Nearly seventy eight per cent of transitions were normative in nature (e.g., scores, selections, entry in a training centre, success in academic examination) and is comparable to other studies (e.g., Samuel & Tenenbaum, 2011). A majority (85%) of these normative transitions was perceived as positive transitions as they were negotiated effectively without any particular assistance (Sinclair & Orlick, 1993).…”
Section: Discussionmentioning
confidence: 73%
“…Although the occurrence of injuries may be seen as a transition generally faced by athletes (e.g., Samuel & Tenenbaum, 2011), it is important to note that their occurrence in this study was reported to be related to (a) dedicating more time to non-athletic aspects of their life (e.g., family, education, new activities) and (b) doubling efforts during the rehabilitation phase for recovering to their best level. All athletes experienced during the course of their career, generally time during the elite stage, at least once an 'invalidating' injury.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…An athlete's career is typically represented by a succession of stages, which reflect the individual's development over time (Samuel & Tenenbaum, 2011). These stages indicate periods of adjustment and are thought to be common, regardless of the athlete's sport, nationality, experience or gender (Cote, 1999;Erpic, Wylleman, & Zupancic, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging the time that elite teams spend off the pitch and practice area (e.g., meetings, travelling to matches, sponsorship and media activities), and therefore the volume of opportunity for conflicting agendas to operate, identifying which individuals assume/are susceptible to such roles (and all other informal roles: cf., Cope et al, 2011) is critical. Significantly, at a time when anxiety will be elevated due to individual-and group-level uncertainty (Samuel & Tenenbaum, 2011) but yet success instantaneously expected by the Board (League Managers Association, 2010), this analysis will need to be highly efficient. Indeed, ensuring that the new vision, systems and practices are delivered from an informed, trusted and respected position is pivotal if any resistance is to be circumvented; particularly when performers and diverse support staffing enjoyed rewarding relationships with the previous incumbent (Ritter & Lord, 2007).…”
Section: Moving Forwardmentioning
confidence: 99%